A Dream and a Plan: A Woman's Path to Leadership in Human Services - Gardella, Lorrie Greenhouse; Haynes, Karen S.; National Association of Social Workers (NASW Press, 2004)
Keywords: Administration; Leadership; Promotions; United States; United States; Career development; United States; Human services; United States; Women executives; United States; Women social workers; Women social workers; dept.swk; faculty_collection

The supervisor in aging services - Corley, C.S.; Takamura, J.; Siegel, E. (Supervision as Collaboration in the Human Services: Building a Learning Culture, 2004)
Journal Abbreviation: Superv. as Collaboration in the Hum. Services: Building a Learning Culture
Keywords: dept.swk

The impact of terrorism, terror and trauma on children: Implications for treatment - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2004)
Keywords: alcohol; antidepressant agent; article; battle injury; behavior therapy; beta adrenergic receptor blocking agent; case report; child; child behavior; cognitive therapy; cultural factor; cyproheptadine; dept.swk; family violence; fear; female; fluoxetine; human; imipramine; immune system; male; nightmare; paroxetine; play therapy; posttraumatic stress disorder; propranolol; psychotrauma; self medication; serotonin uptake inhibitor; sertraline; sexual abuse; street drug; terrorism; tricyclic antidepressant agent; ⛔ No DOI found

Do social workers integrate sociocultural issues in mental health session dialogue?: an exploratory study of cross-cultural practice - Keenan, Elizabeth King; Tsang, A. Ka Tat; Bogo, Marion; George, Usha (Social Work in Mental Health, 2004)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00196 tex.type: [object Object]
Keywords: dept.swk

From sociocultural categories to socially located relations: Using critical theory in social work practice - Keenan, EK (Families in Society-the Journal of Contemporary Human Services, 2004)
This article applies concepts from critical social theories to shift the profession's discourse from the center-margin relations of generalist-multicultural practice to a model of socially located cross-cultural client-worker relationships. Critical theories examine patterns and meanings enacted within and between people in specific social locations at specific points in history that express particular relations of culture, power, and identity. This framework can help social workers listen, explore, conceptualize, and intervene in a more complex and effective manner. The article summarizes key themes in critical theories, redefines how social workers can use knowledge for practice, and concludes with discussion of a case illustration.
12 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000226071200011
Keywords: dept.swk

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-164-803-188-190 tex.type: [object Object]
Keywords: dept.swk

Culture and psychoanalytic theory - Introduction to the book reviews - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000223461500008
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000220649800009
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000221497400008
Keywords: dept.swk